Morphometric Measurements of Several Body Parts of Laying Phase Arabian Chickens - Mohammad Hasil Tamzil; Budi Indarsih; Syamsuhaidi Syamsuhaidi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The objective of this research was to investigate the body measurements of female Arabian chickens during the laying phase. The study utilized a sample of 95 female Arabian chickens, aged 94 weeks, which were housed in battery cages and utilized for egg production. Direct measurements were taken on each chicken, with variables including body weight, head circumference, beak length, comb height, neck length, back length, wing length, chest width, chest depth, upper thigh length, lower thigh length, shank length, shank circumference, the distance between the pubis bones, the distance between the pubic bone and sternum, and the length of the phalanges. The results of the study indicated that the body weight and morphometric measurements of the Arabian chickens were consistent with prior research. Furthermore, the size of the chest, back, neck, and wings displayed a significant correlation with body weight. Therefore, these measurements can be used as indicative markers for predicting the body weight of Arabian chickens.